2015
DOI: 10.3201/eid2105.141427
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology ofPlasmodium falciparumMalaria Outbreak, Tumbes, Peru, 2010–2012

Abstract: Multidrug-resistant parasites from the Amazon region caused the outbreak in the northern coastal region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 26 publications
5
79
0
1
Order By: Relevance
“…falciparum outbreaks in Peru [36] and Panama [37]. To the contrary, we characterized a highly diverse P .…”
Section: Discussionmentioning
confidence: 99%
“…falciparum outbreaks in Peru [36] and Panama [37]. To the contrary, we characterized a highly diverse P .…”
Section: Discussionmentioning
confidence: 99%
“…; Baldeviano et al . ). However, the potential for P. falciparum elimination is much less evident in Africa, the continent with most cases of infection and the highest malaria disease burden.…”
Section: Introductionmentioning
confidence: 97%
“…Clonal P. falciparum outbreaks have been reported from Solomon Islands [45], the highlands of Papua New Guinea [46] or Latin America [38, 47, 48], and in some cases were tracked back to regions of ongoing transmission [38, 48]. Genotyping thus confirmed that cases in previously malaria-free regions were caused by a few imported parasites.…”
Section: Assessing Population Structure To Inform and Guide Malaria Cmentioning
confidence: 84%
“…P. falciparum clonal parasite populations, consistent with outbreaks in regions with very low transmission, occurred in several countries [38, 4548]. In contrast, clonal or near-clonal P. vivax population structure was only reported in a few cases and the findings are difficult to interpret.…”
Section: Genetic Diversity and Population Structure As Surrogate Markmentioning
confidence: 99%
See 1 more Smart Citation